Photoconductivity Multiplication in Semiconducting Few-Layer MoTe2 - Zheng, Wenhao; Bonn, Mischa; Wang, Hai I (Nano letters, 2020)
We report efficient photoconductivity multiplication in few-layer 2H-MoTe2 as a direct consequence of an efficient steplike carrier multiplication with near unity quantum yield and high carrier mobility (∼45 cm2 V–1 s–1) in MoTe2. This photoconductivity multiplication is quantified using ultrafast, excitation-wavelength-dependent photoconductivity measurements employing contact-free terahertz spectroscopy. We discuss the possible origins of efficient carrier multiplication in MoTe2 to guide future theoretical investigations. The combination of photoconductivity multiplication and the advantageous bandgap renders MoTe2 as a promising candidate for efficient optoelectronic devices.